Effect of polyvinyl alcohol on aggregation and flow characteristics of tetra-n-butylammonium bromide and tetra-n-butylphosphonium bromide semi-clathrate hydrate slurries formed under CO2 bubbling. (5th April 2023) - Komatsu, Hiroyuki; Horiguchi, Tatsuya; Sakamoto, Nobuyuki; Tajima, Hideo
Graphical abstract: Highlights: Flow characteristics for CO2 + TBAB or TBPB hydrate slurries with PVA were measured. Flow characteristics and particle shapes assessed the aggregability of slurry. The aggregability of TBPB hydrate slurry was higher than that of TBAB. An appropriate degree of polymerization and concentration of PVA was found. PVA had an anti-agglomeration effect on the slurries formed under CO2 bubbling. Abstract: The rheological properties of tetra- n -butylammonium bromide (TBAB) and tetra- n -butylphosphonium bromide (TBPB) semi-clathrate hydrate (SCH) slurries with polyvinyl alcohol (PVA) were measured using a viscometer to evaluate the anti-agglomeration effect of PVA. The TBAB and TBPB hydrate slurries exhibited a stronger dilatant trend with yield stress and more aggregates with increasing solid fraction. Only TBPB had plate-like crystals, and the frictional force between particles and aggregability in TBPB hydrate slurries were higher than those in TBAB hydrate slurries. The appropriate degree of polymerization (DP) of PVA was 1000, and the appropriate PVA (DP of 1000) concentrations were 0.53 wt% for TBAB hydrate and 1.8 wt% for TBPB hydrate among the SCH solid fractions examined. CO2 bubbling weakens the anti-agglomeration effect of PVA by promoting particle aggregation and enhancing the interactions between plate-like particles. However, adding PVA changed the rheological properties of slurries to a Bingham fluid even under CO2 bubbling conditions.